An Updated Overview of Taxonomy and Phylogenetic History of Tillandsioideae Genera (Bromeliaceae: Poales) - Janaína Gomes-da-Silva; Andrea Ferreira da Costa (Global Journal Of Botanical Science, 2022)
Generic delimitation in Tillandsioideae has been widely discussed over the last past decades, being frequent changes in generic level. Despite the numerous changes at the generic and infrageneric levels in Tillandsioideae there is not yet a study bringing together the history of systematic of the tillandsioid genera. Given the conservation significance and scientific importance of species of the subfamily, it is time revise the generic status of Tillandsioideae. Therefore the purpose of this paper is to provide an updated phylogenetic and systematic history for the genera of Tillandsioideae. We review the fragmentary literature on the phylogeny, classification and taxonomy of Tillandsioideae, and provide an update of these data.